Influence of alcohol consumption on alveolar bone level associated with ligature-induced periodontitis in rats - de Souza, Daniela Martins; Ricardo, Lucilene Hernandes; Kantoski, Karla Zanini; da Rocha, Rosilene Fernandes [UNESP] (FapUNIFESP (SciELO), 2009)
Alcohol consumption is a risk indicator for periodontal disease. The purpose of this study was to morphometrically evaluate the influence of alcohol consumption on alveolar bone level associated with ligature-induced periodontitis in rats. Thirty-six female rats (Wistar, 120 days-old) were randomly divided into three groups that received a daily administration of a water diet (control, n = 12), a 10% alcohol diet (10% ethanol, n = 12) or a 20% alcohol diet (20% ethanol, n = 12). Four weeks after the onset of the experiment, cotton ligatures were placed around the cervix of the upper right second molar in six rats. The other 6 rats in each group remained unligated. The rats were sacrificed four weeks after ligature placement. The maxillary bones were removed and alveolar bone loss was analyzed by measuring the distance between the cementoenamel junction and the alveolar bone crest at 2 buccal and 2 palatal sites on the upper right second molar. Analyses between the ligated and unligated groups showed that the presence of ligature induced alveolar bone loss (p < 0.05). Unligated groups showed no significant differences between each other (p > 0.05). In the ligated groups, rats receiving 20% ethanol showed significantly greater bone loss compared to control rats or rats receiving 10% ethanol. These results demonstrate that alcohol consumption may increase alveolar bone loss in female rats in a dosedependent manner.
Keywords: Alcoholism; Alveolar bone loss; Ethanol; Periodontitis; Rats; alveolar bone loss; animal; disease model; drinking behavior; female; jaw; ligation; pathology; periodontal disease; periodontitis; randomization; rat; risk factor; Wistar rat; Alcohol Drinking; Alveolar Bone Loss; Alveolar Process; Animals; Disease Models, Animal; Female; Ligation; Periodontal Attachment Loss; Random Allocation; Rats, Wistar; Risk Factors